Disease severity during SARS-COV-2 reinfection: a nationwide study. Issue 4 (April 2022) - Mensah, Anna A.; Lacy, Joanne; Stowe, Julia; Seghezzo, Giulia; Sachdeva, Ruchira; Simmons, Ruth; Bukasa, Antoaneta; O'Boyle, Shennae; Andrews, Nick; Ramsay, Mary; Campbell, Helen; Brown, Kevin
Highlights: SARS-CoV-2 reinfections associated with lower risk of death than first infections. Prior infection and immunisation both protect against severe disease at reinfection. Age sex and comorbidities are main risk factors for illness severity at reinfection. Different results in populations at risk of COVID-19 complication and not at risk. Abstract: Objective: We aimed to look at the burden of disease caused by SARS-COV-2 reinfections and identified potential risk factors for disease severity. Methods: We used national surveillance data to collect information on all SARS-CoV-2 primary infection and suspected reinfection cases between January 2020 until early May 2021. Reinfection cases were positive COVID-19 PCR or antigen test, 90 days after their first COVID-19 positive test. We collected information on case demographics, hospital and ICU admission, immunisation status and if individuals were at risk of complication for COVID-19. Results: Deaths reported within 28 days of testing positive were 61% (95% confidence interval: 56% to 65%) lower in suspected COVID-19 reinfection than primary infection cases. In the unvaccinated cohort, reinfections were associated with 49% (37% to 58%) lower odds of hospital admission in cases aged 50 to 65 years in the population not identified at risk of complication for COVID-19, and 34% (17% to 48%) in those at risk. ICU admission at reinfection compared to primary infection decreased 76% (55% to 87%). Individuals at risk and those aged below 50 years, who received at least 1 dose of vaccine against COVID-19, were 62% (39% to 74%) and 58% (24% to 77%) less likely to get admitted to hospital at reinfection, respectively. Conclusion: Prior SARS-CoV-2 infection was associated with lower odds of dying, and both prior infection and immunisation showed a protective effect against severe disease in selected populations. Older age, sex and underlying comorbidities appeared as principal risk factors for illness severity at reinfection. Funding: PHE/UKHSA